Perioperative Surgical Home Model Improves Outcomes in Crohn’s Disease Patients Undergoing Disease-Related Surgery - Hang Xu; Danhua Yao; Yuhua Huang; Haining Fan; Yousheng Li (Gastroenterology Research and Practice)
Background. To evaluate Perioperative Surgical Home (PSH) practice model implementation in Crohn’s disease (CD) patients undergoing disease-related surgery. Methods. A retrospective analysis of CD patients requiring disease-related surgery in the Shanghai Ninth People’s Hospital was undertaken. Subjects were divided into a non-PSH group consisting of 49 patients (June 2016 to November 2017) and a PSH group consisting of 72 patients (December 2017 until May 2019). Conventional treatment was used for the non-PSH group, while in the PSH group, a standardized pre- and postoperative management routine was employed. The postoperative lengths of stay and incidences of postoperative complications were analyzed. Results. There were no significant differences in demographics, reasons for surgery, preoperative BMIs, and preoperative hemoglobin between the two groups (P>0.05). The overall incidence of complications in the PSH group was dramatically lower than that in the non-PSH group (26.4% vs. 44.9%, P=0.035). In the PSH group, postoperative length of stay was significantly shorter than that in the non-PSH group (11.5±5.7 vs. 9.0±6.8, P<0.001). Conclusions. The PSH conditioning routine in CD patients undergoing disease-related surgeries suggests a trend of fewer postoperative complications and shorter lengths of hospital stay. The PSH model may have clinical advantages when applied to CD patients.